Décrocher son diplôme (et l’emploi de ses rêves!) : Comment maîtriser les compétences essentielles menant au succès à l’école, au travail et dans la vie - Klassen, Thomas Richard, 1957-; Dwyer, John, 1948- (Book collections on Project MUSE., 2020)
Going to university is exciting, but it can also be stressful. What courses should I take? What program should I choose? Will I get a job after graduation? This book shows that the best preparation for success on the job, and in life, is succeeding at university. Teamwork, meeting deadlines, overcoming challenges, writing well, and dealing with people are essential in any professional job. These same skills are also vital to becoming a strong student. This practical guide shows you how to master the critical skills and strategies for success at school, work, and in life. Whether you're starting post-secondary studies or are in the middle or about to graduate, this book will help you learn the skills to succeed at school and in the challenging job market. It's meant for all university students, many college and high school students, and their parents. This book will also help you flourish as a student, a professional, and a person. Ultimately, it's about the happiness that comes when you live a thoughtful, balanced, and self-directed life.